2021
DOI: 10.1080/14756366.2021.1929201
|View full text |Cite
|
Sign up to set email alerts
|

Novel chalcone/aryl carboximidamide hybrids as potent anti-inflammatory via inhibition of prostaglandin E2 and inducible NO synthase activities: design, synthesis, molecular docking studies and ADMET prediction

Abstract: 2021) Novel chalcone/aryl carboximidamide hybrids as potent anti-inflammatory via inhibition of prostaglandin E2 and inducible NO synthase activities: design, synthesis, molecular docking studies and ADMET prediction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Docking simulation study was carried out using Discovery Studio 2.5 software (Accelrys Inc., San Diego, CA, USA) [73]. For more details, see Supplementary Materials.…”
Section: In Silico Docking Studymentioning
confidence: 99%
“…Docking simulation study was carried out using Discovery Studio 2.5 software (Accelrys Inc., San Diego, CA, USA) [73]. For more details, see Supplementary Materials.…”
Section: In Silico Docking Studymentioning
confidence: 99%
“…15 Recently, numerous studies have reported that both naturally occurring and synthetic chalcones and dihydrochalcones as anti-inflammatory agents are involved in the inhibition of cytokines and inflammatory mediator production in inflammatory disorders. 13,[16][17][18][19][20] However, limited studies are reported on evaluating the anti-inflammatory activity of chalcones and dihydrochalcones or their structure-activity relationships (SARs).…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are used in several biosynthetic pathways as initial intermediate structures in the production of flavonoids, isoflavonoids, and aurones . A significant part of medicinal chemistry research in the 21st century has been focused on both natural and synthetic chalcones because of their various pharmacological potential including activities and characteristics such as antibacterial, − anti-inflammatory, − analgesic, , anticholinergic, antiplatelet, antiulcer, antioxidant, , antimalarial, anticancer, , antiviral, − antileishmanial, antidiabetic, , immunomodulatory, , aldose reductase inhibition, estrogenic, acetylcholinesterase inhibition, and as non-purine xanthine oxidase inhibitors . Chalcones are highly attractive molecules because of their simple structure, ease of construction, and promising biological applications.…”
Section: Introductionmentioning
confidence: 99%